Convergent and construct validity and test–retest reliability of the Caen Chronotype Questionnaire in six languages. (2nd September 2018) - Laborde, Sylvain; Dosseville, Fabrice; Aloui, Asma; BEN SAAD, Helmi; Bertollo, Maurizio; Bortoli, Laura; Braun, Barbara; Chamari, Karim; Chtourou, Hamdi; De Kort, Yvonne; Farooq, Abdulaziz; Gordijn, Marijke CM; et al.
ABSTRACT: Chronotype questionnaires provide a simple and time-effective approach to assessing individual differences in circadian variations. Chronotype questionnaires traditionally focused on one dimension of chronotype, namely its orientation along a continuum of morningness and eveningness. The Caen Chronotype Questionnaire (CCQ) was developed to assess an additional dimension of chronotype that captures the extent to which individual functioning varies during the day (amplitude). The aim of this study was to provide a multilanguage validation of the CCQ in six world regions (Arabic, Dutch, German, Italian, Portuguese and Spanish). At Time 1, a total of 2788 participants agreed to take part in the study (Arabic, n  = 731; Dutch, n  = 538; German, n  = 329; Italian, n  = 473; Portuguese, n  = 361; Spanish, n  = 356). Participants completed an assessment of the CCQ together with the Morningness-Eveningness Questionnaire (MEQ; Horne & Ostberg 1976) as well as questions related to factors theoretically related to chronotype (age, shift work, physical activity, sleep parameters and coffee consumption). One month later, participants again completed the CCQ. Results showed that the two-factor structure (morningness-eveningness and amplitude) of the CCQ could be replicated in all six languages. However, measurement invariance could not be assumed regarding the factor loadings across languages, meaning that items loaded more on their factors in some translations than in others. Test–retest reliability of the CCQ ranged from unacceptable (German version) to excellent (Dutch, Portuguese). Convergent validity was established through small–medium effect size correlations between the morningness-eveningness dimension of the CCQ and the MEQ. Taken together, our findings generally support the use of the translated versions of the CCQ. Further validation work on the CCQ is required including convergent validation against physiological markers of sleep, health and well-being.